ACCOUNTING POLICY OF UNITED TERRITORIAL COMMUNITIES IN THE CONDITIONS OF DECENTRALIZATION OF POWER AND REFORM OF THE ACCOUNTING SYSTEM - Смірнова, Ірина; Смірнова, Надія (Modern engineering and innovative technologies, 2023)
The work examines the issues of formation and use of the accounting policy of the united territorial communities, which were introduced thanks to the implementation of the decentralization reform in Ukraine. The purpose of this publication is to outline t